ROLE OF PATHYAPATHYAS IN THE ADMINISTRATION OF RASOUSHADHAS (International Journal of Ayurveda and Pharma Research, 2017)
Ayurveda is a medical system which has well developed systems of diagnosis and treatment. It is the only medical system in world, which has apparatus to deal with complete human being, which comprises of mind, body and soul. The treatment is highly personalized according to the patients physical nature, age, immunity, mind power, habit etc. A customized diet, life style, exercise, mental support, breathing and meditation techniques also form the part of the treatment. There is a section in Ayurveda called Rasasastra which describes the use of metals, minerals, and poisons with their actions to combat chronic and complicated diseases. As we all know most of the Rasa drugs are toxic. These pass through extensive processing before they are declared fit for internal use. These preparations are sustaining themselves since centuries in clinical use. A thing that does not adversely affect the body and mind is known as Pathya (wholesome) the diet and regimens opposite to these qualities are said to be Apathya (unwholesome). Many Pathyapathya ahara viharas are mentioned in the Rasa classics. The rationale behind the selection of Aharas and Viharas as Pathya (wholesome) or Apathya (unwholesome) mainly depends on the properties of drugs which are used as Pathya as well as that of drug which is used as medicine. The implied meaning is rules and regulations about diet and movements etc. to be advised by the Physician along with treatment. The medicines are ineffective unless these are followed. In the case of Pathya most probable drug interaction will be synergism and of Apathya dravyas will be antagonism. However, their improper processing, misuse, improper mode of administration may cause adverse effects in the human body. Even though the drugs are in assimilable forms, there should be suitable vehicles for their absorption. Here comes the importance of Pathyapathya while using these metallic forms. Suitable Pathya is necessary while using these Rasa drugs for proper absorption of drug, to reduce its adverse effects, to increase its bio-availability etc.